A sobering examination of the feasibility of aqueous aluminum batteries. Issue 6 (3rd May 2022) - Pastel, Glenn R.; Chen, Ying; Pollard, Travis P.; Schroeder, Marshall A.; Bowden, Mark E.; Zheng, Allen; Hahn, Nathan T.; Ma, Lin; Murugesan, Vijayakumar; Ho, Janet; Garaga, Mounesha; Borodin, Oleg; et al.
Abstract : An in-depth investigation of the solvation structure of the trivalent aluminum cation in Al(OTf)3 solutions reveals major concerns regarding the feasibility of rechargeable aqueous aluminum batteries. Abstract : Aqueous aluminum (Al) batteries are posited to be a cheap and energy dense alternative to conventional Li-ion chemistries, but an aqueous electrolyte mediating trivalent aluminum cations (Al 3+ ) warrants greater scrutiny. This study provides a rigorous examination of aqueous Al electrolytes, with the first compelling evidence for a dynamic octahedral solvation structure around the Al 3+, without Al–OTf contact ion pairs, even at high concentrations. This solvation behavior and the concomitant, transient electrostatic hydrolysis of Al–OH2 ligands contrasts strongly with previously reported water-in-salt electrolytes, and occurs due to the high charge density of the Lewis acidic Al 3+ . Nuclear magnetic resonance spectroscopy and other physicochemical measurements quantitatively reveal how species activity evolves with concentration and temperature. This new understanding exposes practical concerns related to the corrosiveness of the acidic aqueous solutions, the degree of hydration of aluminum trifluoromethanesulfonate (Al(OTf)3 ) salt, and the grossly insufficient reductive stability of the proposed electrolytes (>1 V between HER onset and Al 3+ /Al). Collectively, these factors constitute multiple fundamental barriers to the feasibility of rechargeable aqueous Al batteries.